Step 1

Explanation - Rewrite the given expression,

\(2.14(x-4.06)=2.27-011x\)

Now, simplifying the above expression by breaking the paraentheses bracket, we get,

\(2.14x-4.06\cdot2.14=2.27-0.11x\)

\(2.14x-8.6884=2.27-0.11x\)

\(2.14x+0.11x=2.27+8.6884\)

\(2.25x=10.9584\)

\(x=\frac{10.9584}{2.25}\)

\(x=4.87\)

So, the solution of the above expression is 4.87.

Answer: Hence, the solution of the expression \(2.14(x-4.06)=2.27-0.11x\) is 4.87.

Explanation - Rewrite the given expression,

\(2.14(x-4.06)=2.27-011x\)

Now, simplifying the above expression by breaking the paraentheses bracket, we get,

\(2.14x-4.06\cdot2.14=2.27-0.11x\)

\(2.14x-8.6884=2.27-0.11x\)

\(2.14x+0.11x=2.27+8.6884\)

\(2.25x=10.9584\)

\(x=\frac{10.9584}{2.25}\)

\(x=4.87\)

So, the solution of the above expression is 4.87.

Answer: Hence, the solution of the expression \(2.14(x-4.06)=2.27-0.11x\) is 4.87.